Cutting a Gordian knot of tubeworms with DNA data: the story of the Hydroides operculata-complex (Annelida, Serpulidae) - Sun, Yanan; Al-Kandari, Manal; Kubal, Priti; Walmiki, Nitin; Kupriyanova, Elena K. (Zootaxa, 2017)
Hydroides operculata (Treadwell, 1929) was originally very briefly described from a single specimen as Eupomatus operculata, collected in the Gulf of Aden, Somalia. Later the species was reported from the Mediterranean as a potential Lessepsian migrant. The taxa Hydroides inornata Pillai (1960) from Sri Lanka, as well as H. basispinosa and H. gradata described by Straughan (1967) from Australia, were synonymised with H. operculata based only on their similar opercular morphology, making the latter species’ distribution to include South and East Africa, India, Pakistan, Sri Lanka, Hong Kong, tropical Australia, and the eastern Mediterranean. Here we examined the taxonomic status of H. operculata using standard molecular techniques to determine whether this species is a global invader, a complex of regionally distributed morphologically similar species, or a combination of both. The study revealed three well supported clades suggesting a natural phylogeographic pattern. Thus, we argue that the taxa H. inornata (India and Hong Kong) and H. basispinosa (Australia) should be re-instated to full species, but that the Australian H. gradata should be synonymised with H. basispinosa.